Pengaruh Remunerasi Direksi terhadap Nilai Perusahaan yang Dimediasi oleh Agency Cost pada Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia - Fany, Nurlia Aisyah; Iryanto, Mas Budi Widiyo (Jurnal Manajemen, 2024)
This research aims to determine whether providing compensation to the board of directors can enhance the company's value. The theory utilized in this study is agency theory, which explores the relationship between owners and managers with a separation of power that leads to agency problems. The sample was collected using purposive sampling from companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) during the period of 2019-2021. A total of 144 samples were examined using SmartPLS 3.0 to test the inner model and specific indirect effects. The structural model evaluation, known as the inner model, comprised tests for the determinant coefficient (R2), path coefficient, and hypothesis testing. The research model yielded an R2 value of 11%, indicating its weakness. The research concludes that compensation has a significant positive influence on company value, compensation has a significant negative impact on agency costs, agency costs have a significant negative effect on company value, and agency costs can mediate the relationship between compensation and company value.